Optimal Decisions in Oil Industry - Marius BULEARCA; Cornelia NEAGU; Daniel FISTUNG; Cristian SIMA (Communications of International Proceedings, 2025)
As part of larger research that deals with modeling different aspects concerning oil and gas industry, this paper explores the possibilities of building up operational models for optimal decisions in the oil industry through linear programming aiming at the analysis of investment efficiency in oil and gas industry. Hence, in the beginning, a special focus is placed on revealing some applications that may help us estimate the optimal distribution of investment funds in the oil structures where wells will be drilled in the coming years, for generally, the investment funds allocated to a branch or enterprise are limited. Then, the paper presents a numerical example of a model for the optimal distribution of investments between oil structures. This is just one of many examples of the application of linear programming that has been used to distribute investments in the oil extraction industry. The paper demonstrates that problems may arise regarding the optimal distribution of equipment and material depots in the territory where the wells are drilled, problems regarding the maximum efficiency of certain natural factors.
Keywords: oil and gas reserves; oil and gas wells; optimal decisions; operational models; investment efficiency.